Cardiovascular Stress Induced by Whole-Body Vibration Exercise in Individuals With Chronic Stroke. Issue 7 (1st July 2015) - Liao, Lin-Rong; Ng, Gabriel Y.F.; Jones, Alice Y.M.; Pang, Marco Y.C.
Abstract : Background: Although whole-body vibration (WBV) has sparked tremendous research interest in neurorehabilitation, the cardiovascular responses to WBV in people with stroke remain unknown. Objective: The aim of this study was to determine the acute effects of different WBV protocols on oxygen consumption (V̇o 2 ), heart rate (HR), rate of perceived exertion (RPE), blood pressure (BP), and rate-pressure product (RPP) during the performance of 6 different exercises among people with chronic stroke (time since onset ≥6 months). Design: A repeated-measures design was used. Methods: Each of the 48 participants experienced all 3 WBV protocols in separate sessions: (1) no WBV, (2) low-intensity WBV (peak acceleration=0.96 unit of gravity of Earth [ g ]), and (3) high-intensity WBV (1.61 g ). The order in which they encountered the WBV protocols was randomized, as was the order of exercises performed during each session. Oxygen consumption, HR, and RPE were measured throughout the study. Blood pressure and RPP were measured before and after each session. Results: Low-intensity and high-intensity WBV induced significantly higher V̇o 2 by an average of 0.69 and 0.79 mL/kg/min, respectively, compared with the control condition. These protocols also increased HR by an average of 4 bpm. The 2 WBV protocols induced higher RPE than the control condition during static standing exercise only. Although the diastolic and systolic BP and RPP were increased at the end of each exercise session, the addition of WBV had no significant effect on these variables. Limitations: The results are generalizable only to ambulatory and community-dwelling people with chronic stroke. Conclusions: Addition of high- and low-intensity WBV significantly increased the V̇o 2 and HR, but the increase was modest. Thus, WBV should not pose any substantial cardiovascular hazard in people with chronic stroke.